Analysis of the Clinical Features and Surgical Outcomes of First Branchial Cleft Anomalies. (7th October 2021) - Yang, Runqin; Dong, Chen; Chen, Yang; Liu, Hongsheng; Zhang, Changming; Lai, Yubin; Zha, Dingjun; Han, Yu
Abstract : Objectives: To analyze the clinical features and otologic manifestations of first branchial cleft anomalies (FBCAs) and the disparity between Work's classification, and to explore the relationships between postoperative facial paralysis and features of FBCAs. Study Design: Retrospective clinical study. Methods: A retrospective analysis of 109 patients with FBCAs was conducted, including clinical characteristics and otologic features. Pearson chi‐square tests and Fisher's exact tests were used to compare disparity between Work's classification, and the impact factors of postoperative facial paralysis among 86 patients who were explored in follow‐up. Results: Patients with FBCAs presented with otologic symptoms, including cysts or fistula in the external auditory canal (EAC) and periauricular (43.2%), microtia (3.7%), EAC web (1.8%), otitis media (1.8%), and otorrhea (4.6%). Eighty‐five cases (78.0%) were type I FBCAs and 24 (22.0%) were type II. Compared to type I FBCAs, type II (58.3%) was more likely to be located deep to the facial nerve (FN) and to have superficial parotidectomy on them (79.2%). This difference was statistically significant ( P < .001). FBCAs deep to the FN had a higher incidence of postoperative facial paralysis ( P < .05). Conclusion: The majority of patients (55.0%) had otologic symptoms. The FBCAs of Work type II was commonly deep to the FN and superficial parotidectomy was frequently performed. Postoperative facial paralysis was associated with FBCAs located deep to the FN, but not with Work's type. Level of Evidence: 4 Laryngoscope, 132:1008–1014, 2022